Efficient seamline determination for UAV image mosaicking using edge detection. Issue 8 (3rd August 2018) - Nguyen, Truong Linh; Byun, Younggi; Han, Dongyeob; Huh, Jungwon
ABSTRACT: Image mosaicking of data from individual high-resolution unmanned aerial vehicle (UAV) images is required to obtain sufficient coverage over extensive roads. During the mosaicking process, seamlines may be generated due to differences in illumination or projection between individual images, or the presence of moving objects. This study presents an efficient seamline determination technique based on edge detection for UAV road surface images. The algorithm can be divided into three main steps. First, we detect the edges in the overlapping intensity image within the road boundary. Next, we obtain an automatic seamline passing through regions of non-attraction in areas of overlap. Finally, we adjust the values of the overlapping region using the values of the corresponding individual images by following the coordinates of the seamline detected in the second step, ultimately creating an image mosaic. The experiment using UAV images of a road surface demonstrates that the proposed method produces a satisfactory result. The proposed method can be applied for quick mosaicking of UAV images intended for maintaining road safety.